LIMITATIONS OF THE STATE'S OBLIGATIONS IN PROVIDING CONSULAR PROTECTION TO INDONESIAN CITIZENS WHO HAVE BEEN DEPORTED BASED ON THE 1963 VIENNA CONVENTION - Muhammad Bahagia; Harisman (RADJA PUBLIKA, 2026)
Deportation of foreign nationals is an administrative action taken by the receiving country as part of immigration law enforcement based on the principle of state sovereignty. In practice, deported Indonesian citizens (WNI) often apply for protection to Indonesian consular representatives abroad. This situation has given rise to debate regarding the extent of the obligations of the country of origin to provide consular protection, especially when the deportation decision has been made by the receiving country's authorities. This study aims to analyze the obligations and limits of state consular protection for deported Indonesian citizens based on the 1963 Vienna Convention on Consular Relations, as well as to examine the challenges and practices of Indonesian consular protection. This study uses a normative legal research method with a legislative approach and a conceptual approach. The results show that consular protection is an international legal obligation of the country of origin, but is limited and cannot intervene in the receiving country's authority to impose deportation. The consular role focuses more on consular access, assistance, information provision, and administrative and humanitarian facilitation. This study concludes that strengthening legal education and public understanding of consular functions is a preventive measure to minimize immigration violations and erroneous expectations regarding the state's role in the deportation process.